PERENIALISME DALAM PERSPEKTIF PENDIDIKAN KONTEMPORER: MENJAGA NILAI-NILAI UNIVERSAL DI ERA GLOBALISASI - Azimatu Syamimah; Siti Rahayu; Alya Dwi Ramadhani; Muhlisin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Education is the main pillar in character building and human civilization, especially amidst globalization which brings challenges of moral crisis and truth relativism. This article aims to explore the relevance and implementation of perennialism philosophy in contemporary education. Ontologically, perennialism views reality as constant; epistemologically, it emphasizes rational processes and critical thinking; and axiologically, it places universal moral values and absolute truth as the eternal foundation of human behavior. Using the Systematic Literature Review (SLR) method by analyzing scientific journal articles published from 2021 to 2025, the research finds that in the digital era, perennialism functions as a moral anchor and an information filter to counter hoaxes through the reinforcement of logic and rationality. Its modern implementation includes the use of the Great Books method, Socratic dialectics, and the repositioning of teachers as moral role models. The adaptation strategy requires the wise integration of technology, where technology is positioned as a means while humans remain the main end of education. Therefore, perennialism remains relevant as a philosophical foundation to produce individuals who are intellectually intelligent while possessing strong integrity and character in the global era.